Perivellosa disease massive fibrin deposition, association with Down syndrome: case report and literature review - Ochoa, Cristobal Barragan; Lara Sanchez, Raul D.; Araiza Navarro, Junior J.; Tolentino Sosa, María I.; Alvarez Dominguez, Tania P.; Villanueva, Roberto Rivera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The disease perivellosa massive fibrin deposition (MPFD), is a condition characterized by uncontrolled mainly fibrin deposition intervillous space. The incidence worldwide is 0.028% per 1000 live births, there is only one case report where this condition is associated with trisomy 21, in our country there are no reports of this disease. The MPFD has high morbidity, obstetric mortality, recurrence, as well as neurodevelopmental significance of newborns. The etiology until the moment is unknown, difficult diagnosis and management for the obstetrician. The aim is to report MPFD association with trisomy 21 (T21) and a review of the medical literature regarding this condition.